Production System of Peranakan Etawah Goat under Application of Feed Technology: Productivity and Economic Efficiency - Sodiq, A; Setianto, NA (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2009)
Feed resources are the major constraint in increasing goat production in the village. The main constraints to goat raising are related to feeds (i) the high cost of transport of crop residues and grass to the homesteads, (ii) the low nutritive value of feeds used, particularly in the dry period. This research was design to evaluate goat productivity and economic efficiency of goat farming under application of feed technology production system in Peranakan Etawah goat farmer group of Gumelar Banyumas Central Java. All farmers were taken as respondents using census methods. On farm research with participative focused group discussion, indepth interview, and farm observation. Descriptive analysis and independent t test methods were used to analyze the data. Results of this study showed that there was a significant improvement Â goat productivity on production system with the application of feed technology. Body weight at weaning, survival rate till weaning, and doe productivity were increased 7%, 2% and 5%, respectively. There was no evidence of significant different of farmers income and economic efficiency before and after the applied feed technology (P>0.05). The calculation was based on cash flow.Â Before application, farmers income per year and economic efficiency were Rp14.404.520,00 and 1.21, then insignificantly improve into Rp16.487.100,00 and 1.27, respectively. (Animal Production 11(3): 202-208 (2009)Â Key Words: Livestock production system, Peranakan Etawah goat, feed technology aplication, productivity and economic efficiency